Proceedings of the 1st International Scientific Conference - Sinteza 2014 2014
DOI: 10.15308/sinteza-2014-368-374
|View full text |Cite
|
Sign up to set email alerts
|

Internet u nastavi i učenju

Abstract: Abstract:Internet i sa njim sve više povezan Web 2.0 aplikacije, ne mogu da se izostave iz svakodnevnog života današnje dece i omladine. Mladi i deca odrastaju u medijskom okruženju, korištenje tehničkih inovacija i konvergento okruženje medijima predstavlja značajan izazov i (razvojni) zadatak kako za njih same, tako i za njihove roditelje i školu. Škola će se, sve više, baviti mogućnošću razvoja kompetencija za samostalno učenje učenika, kako bi im pomogla, da se adekvatno nose sa zahtevima radnog života. No… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…Although there were many divided opinions about their usage and efficiency, the time when the whole world fell into the Covid crisis definitely showed that their usage is very important, so important that these applications present the only possibility for online teaching. Researches confirmed that the usage of these applications increased in last past years, especially in the last year and in the current year (Andevski, Vidaković, Arsenijević, 2014).…”
mentioning
confidence: 63%
“…Although there were many divided opinions about their usage and efficiency, the time when the whole world fell into the Covid crisis definitely showed that their usage is very important, so important that these applications present the only possibility for online teaching. Researches confirmed that the usage of these applications increased in last past years, especially in the last year and in the current year (Andevski, Vidaković, Arsenijević, 2014).…”
mentioning
confidence: 63%
“…A study on attitudes toward teachers' and students' use of ICT in teaching process (Džigurski, Simić, Marković, Šćepanović, 2013) indicated a significantly more positive attitude toward the use of computers among younger teachers. Another study (Andevski, Vidaković, Arsenijevič, 2014) shows that 80% of teachers are using computers in teaching, and yet another (Lindberg, Olofsson, & Fransson, 2016) shows that the use of computers provides time and space flexibility which is why the computer has been used in teaching.…”
Section: Introductionmentioning
confidence: 99%
“…The fact that teachers have a positive attitude to the use of digital technologies and that the main obstacle to the application of digital technologies for them is the lack of digital skills has been demonstrated by many studies -Innovative learning environmentsfor schools (Ramboll Management , 2004), The ICT Impact Report (Balanskat & Blamire, 2007), Sipilä (2014), Lindberg et al (2016). A study carried out by Andevski et al (2014) showed that the large number of teachers (up to 80%) use the Internet for teaching.…”
Section: Introductionmentioning
confidence: 99%